Demonstrate The Use and Embodiment of Body Language in The Official Meeting Between Nichirvan Barzani and Emmanuel Macron - Khaleel, Kawan; Abdullah, Abdulsalam; Mohammed, Fakher (Humanities Journal of University of Zakho, 2021)
The current research study attempts to demonstrate the use and embodiment of body language in the official meeting between Nichirvan Barzani and Emmanuel Macron which was held on March 30th, 2021. As it is clear, body language is regarded as one of the crucial factors in meetings and assemblies and carries rich meanings which in turn reflect the successfulness of the meeting. This study is entitled (The analysis of body language in the official meeting held between (Nechirvan Barzani) and (Emmanuel Macron). The Paris meeting which was held on March 30th 2021 is taken as a model. The body language used in the meeting was analyzed utilizing the descriptive approach to pinpoint the pivotal function that this language performs in order to identify the extent to which the meeting had positive or negative results. The above approach was also used to show how this language can embody the success of communication because each physical gesture or movement has a particular meaning and denotation to express. In the end, it was concluded that the gestures, signals, and the movements of the body used between both presidents, in general, indicated positive meanings. Moreover, it was apparent from the use of gestures that there is a strong friendly relationship between the two presidents.